1989
DOI: 10.1159/000234806
|View full text |Cite
|
Sign up to set email alerts
|

Role of Local IgA Antitoxin-Producing Cells for Intestinal Protection against Cholera Toxin Challenge

Abstract: We examined in mice, perorally immunized with cholera toxin (CT) or cholera B subunit (CTB), the association between protection against intestinal toxin challenge and frequency and function of gut mucosal IgA antitoxin-forming cells. The in vitro production of IgA antitoxin by isolated cells and the toxin-neutralizing ability of culture supernatants were determined. Repeated oral immunizations with CT gave rise to high numbers of IgA antitoxin ‘spot-forming’ cells (SFC) in the lamina propria as well as to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…IgA antibodies directed against CT have also been implicated in protection against V. cholerae-induced disease (7,10,16,19), but the relative importance of anti-CT IgA in protection has not been well defined (13,14). In several experimental systems, the presence of anti-CT IgA antibodies in secretions was associated with protection of the intestine against orally administered CT (16-18, 28-30, 37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IgA antibodies directed against CT have also been implicated in protection against V. cholerae-induced disease (7,10,16,19), but the relative importance of anti-CT IgA in protection has not been well defined (13,14). In several experimental systems, the presence of anti-CT IgA antibodies in secretions was associated with protection of the intestine against orally administered CT (16-18, 28-30, 37).…”
Section: Discussionmentioning
confidence: 99%
“…After ingestion, V. cholerae enters the small intestine, adheres to mucosal surfaces, and forms colonies that secrete cholera toxin (CT), the agent responsible for the massive secretory diarrhea that is the hallmark of the disease (7,14,22). Colonization of the intestine by V. cholerae evokes a mucosal immune response in the host, including secretion of immunoglobulin A (IgA) antibodies (sIgA) that are thought to be involved in limiting the duration of the primary infection and in imparting resistance to subsequent oral challenge (10,13,(16)(17)(18)(19)(20)33). This response includes polyclonal sIgA antibodies directed against both CT and bacterial surface components including the outer membrane lipopolysaccharide (LPS) (10,15,19).…”
mentioning
confidence: 99%
“…There is considerable evidence, however, that antitoxin antibodies play the primary role in protection against oral toxin challenge. Polyclonal anti-CTB antibodies have been shown to be capable of toxin neutralization in both rabbit skin permeability tests and ligated intestinal loop models (26,33). Recently, it was demonstrated that protection of intestinal loops against intraluminally injected CT in animals orally immunized with CT is CD4 T cell dependent (14).…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated (24) that even repeated oral immunizations with CT-B devoid of any CT did not induce any significant protection, despite the presence of some anti-CT Ab responses. To obtain significant, but weak, gut protection, the CT-B oral immunizations required the presence of at least 5% CT (24). Hence, the mean degree of intestinal protection observed after our anti-id MAb2 immunizations was indeed remarkable.…”
Section: Resultsmentioning
confidence: 80%
“…A potential problem with our data could be the lack of correlation (data not shown) between individual serum or biliary anti-CT Ab3 titers, on the one hand, and the percentage of protection against the gut CT challenge in the same animals on the other hand. Such a correlation, which has been obtained with oral immunizations directly with CT or CT-B mixed with traces of CT (24), would nevertheless seem desirable if anti-id vaccination is to become more generally acceptable. On the other hand, when protection was obtained with other anti-id immunization models, correlations between degree of protection and Ab titers were rather poor (29) or not even mentioned.…”
Section: Resultsmentioning
confidence: 96%